Diagnostic Value of Liquid-Based Cytology in Urothelial Carcinoma Diagnosis: A Systematic Review and Meta-Analysis. - You Luo; Dong-Li She; Hu Xiong; Li Yang; Sheng-Jun Fu (PLoS ONE)
Objective To evaluate the value of liquid-based cytology (LBC) in the diagnosis of urothelial carcinoma. Method Diagnostic studies were searched for the diagnostic value of LBC in urothelial carcinoma in PubMed, Embase, Cochrane Library, Web of Science, CBM and CNKI. The latest retrieval date was September 2014. The data were extracted and the quality of the included studies was independently assessed by 2 reviewers. Stata 13 software was used to perform the statistical analysis. The research was conducted in compliance with the PRISMA statement. Result Nineteen studies, which included 8293 patients, were evaluated. The results of the meta-analysis showed that the pooled sensitivity and specificity of LBC were 0.58 (0.51-0.65) and 0.96 (0.93-0.98), respectively. The diagnostic odds ratio (DOR) was 31 (18-56) and the area under the curve (AUC) of summary receiver operating characteristic (SROC) was 0.83 (0.80-0.86). The post-test probability was 80% when a positive diagnosis was made. Compared with high grade urothelial carcinoma (HGUC), the sensitivity of detecting low-grade urothelial carcinoma (LGUC) was significantly lower, risk ratio of sensitivity was 0.54 (0.43-0.66), P<0.001. However, no significant sensitivity improvement was observed with LBC when compared with traditional cytospin cytology, risk ratio was 1.03 (0.94-1.14), P = 0.524. Conclusion Despite LBC having a pooled 58% positive rate for urothelial carcinoma diagnosis in our meta-analysis, no significant improvement in sensitivity was observed based on the studies evaluated. Further research is needed to validate these findings.